Ventromedial hypothalamus lesions increase the dipsogenic responses and reduce the pressor responses to median preoptic area activation - Bastos, R.; Menani, José Vanderlei [UNESP]; Saad, W. A.; Renzi, Antonio [UNESP]; Silveira, JEN; Camargo, LADA (Elsevier B.V., 1997)
In this study, we investigated the participation of adrenergic receptors of the median preoptic area (MnPO) and the participation of ventromedial hypothalamus (VMH) in angiotensin II- (ANG II)-induced water intake and presser responses. Male rats with sham or electrolytic VMH lesions and a stainless steel cannula implanted into the MnPO were used. Noradrenaline, clonidine (an alpha(2)-adrenergic receptor agonist), or phenylephrine (an alpha(1)-adrenergic receptor agonist) injected into the MnPO of sham-lesioned rats reduced water ingestion induced by ANG II injected into the same area. In VMH-lesioned rats ANG II-induced water intake increased with a previous injection of noradrenaline, phenylephrine, or isoproterenol. The presser response induced by ANG II injected into the MnPO was reduced in VMH-lesioned rats, whereas the presser response induced by clonidine was abolished. Previous treatment with noradrenaline and phenylephrine into the MnPO of sham-lesioned rats produced a presser response, and a hypotensive response was obtained with the previous administration of noradrenaline, phenylephrine or isoproterenol into the MnPO of VMH-lesioned rats. These results show that VMH is essential for the dipsogenic and presser responses induced by adrenergic and angiotensinergic activation of the MnPO in rats. (C) 1997 Elsevier B.V.
Keywords: water intake; arterial pressure; ANG II; adrenergic agonists; MnPO; VMH